Ambient Noise Surface Wave Reverse Time Migration for Fault Imaging. Issue 12 (22nd December 2020) - Li, Haipeng; Li, Junlun; Gu, Ning; Gao, Ji; Zhang, Haijiang
Abstract: Ambient noise tomography (ANT) has become a routine method to image shear‐wave velocity variations at different scales. However, ANT can only resolve smooth velocity variations and cannot give high‐resolution images of the subsurface discontinuities. Here we propose a novel Transmitted Surface Wave Reverse Time Migration (TSW‐RTM) method to directly image fault planes using the empirical surface wave Green's functions retrieved from ambient noise. Our proposed method can directly utilize the reconstructed surface wave waveforms from seismic noise cross‐correlations to image the sharp fault discontinuities with the seismic imaging principle. Compared to the conventional ambient noise tomograms, the migrated images from our proposed method delineate fault planes with much higher resolution and certainty for interpretations. The synthetic tests with different fault zone models demonstrate the effectiveness and accuracy of our novel fault imaging method. The proposed TSW‐RTM method is also applied to image two different segments of the Tanlu fault zone (TFZ) in eastern China, using the surface waves retrieved from the ambient noise data recorded by dense seismic linear arrays deployed across the TFZ. Our ambient noise imaging results are consistent with previous studies in the same areas regarding the fault plane positions and dips. Both synthetic tests and real data applications demonstrate that our method is very useful for fault characterizations in areas where active and passive seismic data are not available. Our proposed TSW‐RTM method opens up new ways to utilize the seismic ambient noise for imaging subsurface fault zone structures. Key Points: A novel Transmitted Surface Wave Reverse Time Migration method is proposed to directly image the sharp fault discontinuities The reconstructed surface waves from seismic noise cross‐correlations are used to image fault planes with the seismic imaging principle The proposed method opens up new ways to utilize the seismic ambient noise for imaging subsurface fault zone structures